A Murine Neural-Specific Homolog Corrects Cholinergic Defects inCaenorhabditis elegans unc-18 Mutants - Gengyo-Ando, Keiko (J Neurosci, 1996)
Caenorhabditis elegans UNC-18 protein, homologous to yeast Sec1p, is important in neurotransmitter release, because theunc-18 mutation leads to severe paralysis and presynaptic acetylcholine (ACh) accumulation. To examine the functional conservation in mammals, we tried to isolate unc-18isoforms from mouse and human brain cDNA libraries and obtained two classes of isoforms—neural genes and ubiquitous genes. Neural genes were identical to Munc-18 (also known as n-Sec1 or rbSec1), identified in rat and bovine brains as a syntaxin-binding protein. According to “Munc-18” terminology, we call the neural genes Munc-18-1 and the ubiquitous genes Munc-18-3. These mammalian isoforms exhibit 58% (Munc-18-1) and 42–43% (Munc-18-3) amino acid sequence identity with UNC-18. Next, we constructed transgenic unc-18mutants to test biological activity of mouse Munc-18-1 and Munc-18-3 under the control of C. elegans unc-18promoter. Munc-18-1 compensates for severe locomotion disability and cholinergic defects, e.g., abnormal sensitivities to cholinesterase inhibitors and cholinergic receptor agonists inunc-18 mutants, but Munc-18-3 fails. These data suggest that Munc-18-1 and C. elegans unc-18 may play positive roles in ACh release and that the molecular mechanism of neuronal regulated secretion has been partially conserved from nematodes to mammals.